2016
DOI: 10.1177/2050640615604775
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter survey on the use of device‐assisted enteroscopy in Portugal

Abstract: Background: Device-assisted enteroscopies (DAEs) are recent endoscopic techniques that enable direct endoscopic smallbowel evaluation. Objective: The objective of this article is to evaluate the implementation of DAEs in Portugal and assess the main indications, diagnoses, diagnostic yield, therapeutic yield and complication rate. Methods: We conducted a multicenter retrospective series using a national Web-based survey on behalf of the Portuguese Small-Bowel Study Group. Participants were asked to fill out tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
(72 reference statements)
4
18
0
Order By: Relevance
“…We have also found that patients with cardiovascular disease have a higher diagnostic and therapeutic yield. Vascular angioectasia was also the commonest finding in patients with OGB, as previously reported in the literature [1,2]. We feel that DBE should be carefully considered in patients with OGB even with the presence of significant cardiovascular disease prior to the decision of medical therapy.…”
Section: Letter To the Editorsupporting
confidence: 54%
See 1 more Smart Citation
“…We have also found that patients with cardiovascular disease have a higher diagnostic and therapeutic yield. Vascular angioectasia was also the commonest finding in patients with OGB, as previously reported in the literature [1,2]. We feel that DBE should be carefully considered in patients with OGB even with the presence of significant cardiovascular disease prior to the decision of medical therapy.…”
Section: Letter To the Editorsupporting
confidence: 54%
“…The authors suggest that anterograde DBE may be the most cost-effective approach in the evaluation and treatment of elderly patients with OGB and vascular lesions. A large proportion of patients with OGB are not only elderly but with significant comorbidity, particularly cardiovascular disease [2]. Pasha et al also elude that although medical therapy has not been proven to be effective for the management of small bowel bleeding, it is reserved for patients with significant comorbidity [1].…”
Section: Letter To the Editormentioning
confidence: 99%
“…In Western countries, SBVL represent the most frequent small bowel finding in patients with OGIB (10). (3) The exact prevalence of angioectasias is unclear because most patients are asymptomatic and only 10% of all patients will experience a symptomatic gastrointestinal bleed during their lifetime (13,17,18). (5,7,11) The clinical presentation of angioectasias includes overt bleeding or iron deficiency anemia, which represent the main indications for endoscopic treatment (3,13,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports suggest a reduction in rebleeding rates in patients who received additional therapy. This is probably as a result of intensive enteroscopy and increased complete enteroscopy rates, which may allow the treatment of SBVL that were not reached in previous examinations as there were multiple lesions occurring throughout the gastrointestinal tract (15,18,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic and therapeutic yield of device-assisted enteroscopy for OGIB was J Gastrointestin Liver Dis, December 2017 Vol. 26 No 4: 369-374 reported to be 69% and 52% in a multi-centre retrospective study [13]. The presence of an overtube at DBE allows deeper examination of the small bowel.…”
Section: Introductionmentioning
confidence: 99%